Extraction and Purification of albumin from Hunan plasma (Baghdad Science Journal, 2011)
This study includes adescription of Human serum Albumin by amodified using ion- exchange chromatography with manipulated comparison with cold ethanol precipitation method , It has been nticed that this procedure is superior orer the classical method . The Final yield by the new method 69.32% with purity of 83.42% compared with cohn which yield 60.30 % with purity of 80.7 % . The new method prored that it suitable for the pusi Fication of such material because it yield no precipitation material and it increases the Final yield of albumin solutions . • Human serum Albumin .• Albumin purification .• Ion – exchange chromatography .• Human plasma .• Albumin extraction .